Radiation-Induced Correlation between Molecules Nearby Metallic Antenna Array - Yoshiki Osaka; Nobuhiko Yokoshi; Hajime Ishihara (International Journal of Antennas and Propagation)
We theoretically investigate optical absorption of molecules embedded nearby metallic antennas by using discrete dipole approximation method. It is found that the spectral peak of the absorption is shifted due to the radiation-induced correlation between the molecules. The most distinguishing feature of our work is to show that the shift is largely enhanced even when the individual molecules couple with localized surface plasmons near the different antennas. Specifically, we first consider the case that two sets of dimeric gold blocks with a spacing of a few nanometers are arranged and reveal that the intensity and spectral peak of the optical absorption strongly depend on the position of the molecules. In addition, when the dimeric blocks and the molecules are periodically arranged, the peak shift is found to increase up to ~1.2 meV (300 GHz). Because the radiation-induced correlation is essential for collective photon emission, our result implies the possibility of plasmon-assisted superfluorescence in designed antenna-molecule complex systems.